Interaksi Pemberian Pupuk Controlled Release dengan Soil Conditioner terhadap Pertumbuhan Vegetatif dan Serapan Hara Nitrogen serta Fosfor Bibit Kelapa Sawit - Hamzah, Muhammad; Adiwirman, Adiwirman; Puspita, Fifi (Jurnal Agro Teknologi Tropika, 2015)
The aim of the study is to determine the effect of controlled release fertilizer application, soil conditioner and theinteraction of these two treatments on vegetative growth and nutrient uptake nitrogen and phosphorus of oil palmseedlings. The experiment was conducted in Research Department of First Resources Ltd, Riau in April 2013 untilJanuary 2014. Research design of the study used a randomized complete block design (RCBD) two factors with 3replications. The first factor was the controlled release fertilizer application/CRF (P) as follows: P1: SR NPKMg 15-15-6-4, P2: CRF NPKMg 17-8-9-3, P3: CRF NPKMg 18-8-8-2, P4: CRF NPKMg 20-6-14-3. The second factor was theapplication of soil conditioner (H) is H0 : Control, H: Liquid formulations of Bacillus sp, H2: Humic acid granularformulations, H3: Liquid formulations endopalma. The results showed that fertilization treatment CRF NPKMg 20-6-14-3 is treatment that gives the higher all vegetative growth parameters and all nutrient uptake parameters. Soil conditionertreatment granular humic acid gives the higher for crown dry weight, root dry, root volume and plant height. Interactionof CRF NPKMg 20-6-14-3 with control gives the higher for seed quality index, number of leaves, stem diameter, leaf areaand nutrient uptake parameters include nitrogen and phosphorus.